The effect of leadership style and organizational culture on employee motivation of the Tangerang City DPRD secretariat - Yuyun Santika; Herayati Herayati; Martinus Wayu Purnomo (International Journal of Applied Finance and Business Studies, 2023)
The Tangerang City DPRD (Regional People's Representative Council) was established in accordance with Law No.2 of 1993 that led to the creation of Tangerang Municipality. Collaborating closely with the local government, the DPRD plays a pivotal role in shaping the effectiveness of the autonomous region's governance. As a governing and developmental entity, the DPRD holds significant influence.This study focuses on the impact of leadership style and organizational culture on employee motivation within the Tangerang City DPRD secretariat. The research employs a quantitative approach, encompassing a population of 64 employees. From this pool, 39 employees were selected as respondents for the study. Using statistical methods like multiple linear regression and SPSS 25.0, the data was analyzed.The findings revealed that both leadership style and organizational culture positively and significantly affect employee motivation. Leadership style exhibited a notable impact with a value of 5.920, while organizational culture's effect stood at 2.349. Moreover, their combined influence was even more pronounced, with a value of 40.438. The regression model expressed as Y = 10.453 + 0.865 X1 + 0.397 X2 demonstrates that leadership style and organizational culture collectively elevate employee motivation at the Tangerang City DPRD secretariat. This study underscores the importance of effective leadership and a nurturing organizational culture in enhancing employee motivation within the context of the DPRD.